An Ethnobotanical Survey of Medicinal Plants used in the Preparation of “Atikédi”: Local Alcoholic Beverages Commonly Consumed in Lomé Togo - Afanyibo Yaovi-Gameli; Koudouvo Koffi; Esseh Komlavi; Agbonon Amegnona; Tozo Koffi; Gbeassor Messanvi (European Scientific Journal, ESJ, 2018)
Ethnobotanical relevance: Local alcoholic beverages “Atikédi” are produced in Lomé and consumed not only for pleasure but also for therapeutic purposes. They are produced out of “Sodabi”, distilled palm wine, mixed with plant organs. However, the exact composition of these beverages and the diseases they are supposed to treat are poorly documented to date in Togo. Aim of the study: To make an inventory of plants used by “Atikédi” beverages producers in Lomé. Materials and methods: Data collection was made through Semi Structured Interview. Data processing and analysis were done using Excel and Epi Info. Results: 267 outlets were identified with a predominance of stores (53.18%). 192 women and 75 men were interviewed. They belonged to 12 different ethnic groups with the majority being Ewe (127) and Ouatchi (71). Their age range varied from 25 to 70 years with an average of 42.6±7.9 years. 61 plants species were recorded belonging to 58 genera and 35 families. The most represented family was the Apocynaceae with five species followed by the Rutaceae and the Poaceae with four species each. Among 43 diseases managed by the plants, bacterial infections (ICF=0.95) and sexual weakness (ICF=0.95) were the most important pathologies. Conclusion: Producers of “Atikédi” used a wide range of medicinal plants. Pharmacological and toxicological studies of these plants will improve the quality of care provided by traditional medicine.